Double Dexter [compact disc, unabridged] : a novel - Lindsay, Jeffry P. (Random House : Books on Tape, 2011)
Dexter Morgan is not your average serial killer. He enjoys his day job as a blood spatter analyst for the Miami Police Department, but he lives for his nighttime hobby of hunting other killers. Dexter is therefore not pleased to discover that someone is shadowing him, observing him, and copying his methods. Dexter is not one to tolerate displeasure; in fact, he has a knack for extricating himself from trouble in his own pleasurable way.